Formation of artistic ways of activities of creative activity of students in classes of the discipline "artistic paper processing" (Pedagogy of Higher and Secondary Education, 2006)
The basic rules (situations) of an experimental research of process of formation of professional ability of the future teacher of fine arts to art training of the schoolboys in conditions of system of art-pedagogical education art considered (examined).
Keywords: professional ability; artistic teaching